Care Behavior on Postmenopausal During Covid-19 Pandemic in The Medan Johor District Area - Siti Saidah Nasution (Talenta Publisher, 2023)
Reproductive health issues, especially maternal and infant health, are a priority and require special care during the COVID-19 pandemic. One of the groups at high risk of contracting the COVID-19 virus is people in the elderly age group, especially mothers in the menopause stage, which is categorized as a comorbid group. An assessment of the knowledge and attitudes of postmenopausal mothers in health care is important to maximize action in the treatment and prevention of disease. This type of research is a descriptive study that aims to describe behaviors, especially the knowledge and attitudes of postmenopausal mothers. The population of all menopausal mothers in the Medan Johor sub-district with a sample of 128 people. Data collection was carried out using questionnaires, which consisted of demographic data, and knowledge and attitude data. Univariate data analysis using frequency distribution and presentation. The results of the study found that the knowledge of postmenopausal mothers was in a low category, namely around 48%, and negative attitudes of 52% related to health care during the COVID-19 pandemic.